2013
DOI: 10.1021/ma400333f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymer Molecular Weight on the Parabolic and Linear Growth Regime of PDADMAC/PSS Multilayers

Abstract: The buildup of polyelectrolyte multilayers is investigated in solution with multiple angle null-ellipsometry. Polyanion poly(styrenesulfonate) (PSS) and polycation poly(diallyldimethylammonium) (PDADMAC) are adsorbed sequentially from 0.1 M NaCl solution. First the films grow parabolically. After N trans deposited PDADMAC/PSS layer pairs a transition from a parabolic to a linear growth occurs. For molecular weights above a threshold (M w(PSS) > 25 kDa and M w(PDADMAC) > 80 kDa), N trans is 15, the thickness pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
119
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(133 citation statements)
references
References 34 publications
(74 reference statements)
12
119
2
Order By: Relevance
“…These characteristic nanostructures were already reported for higher layer numbers on silica substrates 45. The high molecular weight and the fact that PD is completely charged leads to a strong electrostatic repulsion of the polymer segments and to a coiled surface conformation(Figure 2 D, G) 46,47. As the bi-layered sample already showed this characteristic nanostructure, it can be assumed that even a single layer of PD is most likely sufficient to completely cover the surface features of the gold substrate.…”
supporting
confidence: 71%
“…These characteristic nanostructures were already reported for higher layer numbers on silica substrates 45. The high molecular weight and the fact that PD is completely charged leads to a strong electrostatic repulsion of the polymer segments and to a coiled surface conformation(Figure 2 D, G) 46,47. As the bi-layered sample already showed this characteristic nanostructure, it can be assumed that even a single layer of PD is most likely sufficient to completely cover the surface features of the gold substrate.…”
supporting
confidence: 71%
“…This growth behavior was often described in literature. 32,33 Because of the low ionic strength (0.1 M NaCl) during preparation, the nonlinear growing regime is small in terms of thickness. The thickness increment grows from 1.0 to 4.0 nm at the end of the nonlinear growing regime.…”
Section: Thickness Of Pss/pdadmac Pems At Different Rh Values and In mentioning
confidence: 99%
“…The PEM build‐up can be characterized by different growth mechanisms: The adsorbed mass m ( n ) and/or the total film thickness d ( n ) as a function of the number of adsorbed bilayers, n , respectively, can increase either linearly, exponentially, or parabolically . Multilayers from synthetic polyelectrolytes, which are characterized by high charge densities (e.g., PSS/PAH), mostly grow in a linear fashion, whereas multilayers consisting of natural polyelectrolytes having low charge densities but large hydration shells (e.g., poly‐ l ‐glutamic acid (PGA) and poly‐ l ‐lysine (PLL) or hyaluronic acid and PLL) tend to grow exponentially.…”
Section: Introductionmentioning
confidence: 99%
“…However, deviating from this general classification, supralinear growth was observed for multilayer systems made from synthetic polyelectrolytes under certain conditions: In the case of PDADMA/PSS multilayers Guzmán et al observed linear growth at low salt concentrations, and exponential growth at high salt concentrations . Nestler et al investigated PDADMA/PSS multilayers and found that above a certain salt concentration the initial growth law is parabolic up to a critical layer number, above which it changes to a linear law. The critical layer number depends on the molecular weight .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation